MODELLING THE DECISION TO USE BNI KCP JUWANA BNI CUSTOMERS WITH TECHNOLOGY ACCEPTANCE MODEL - Yeti Kristianti (Jurnal Akuntansi dan Pajak, 2023)
Advances in technology have made the banking industry invest capital in developing services that are believed to increase the ease and speed of transactions for its customers, such as m-banking services. However, based on the phenomenon that occurred, the percentage of m-banking users at BNI KCP Juwana customers during the last six months has not increased significantly and is still far from the target set by the bank, which is at least 60% of total customers. gap in the Technology Acceptance Model in the form of inconsistent results in previous studies so that this phenomenon is interesting to study. The purpose of this study was to analyze the effect of perceived ease of use, perceived usefulness on attitudes toward using m-banking and the decision to use m-banking on BNI KCP Juwana customers. The population chosen in this study were all 30,223 BNI KCP Juwana customers who have used BNI m-banking. The number of respondents used in this study was 114 customers of BNI KCP Juwana. The sampling technique in this research is the purposive sampling. The data collection method is by using a questionnaire. The data analysis method used is Structural Equation Modeling. Based on research, perceived ease of use has a positive effect on perceived usefulness, perceived ease of use has a positive effect on attitude toward using, perceived usefulness has no effect on attitude toward using, perceived ease of use has no effect on usage decisions, perceived usefulness has a positive effect on decisions use and attitude toward using have a positive effect on usage decisions. Keywords: perceived ease of use, perceived usefulness, attitudes toward using m-banking, decision to use m-banking